An Analysis of Science Literacy Ability Elementary School Students - Dzuhrotul Ulumiyah; Mohammad Syarif Sumantri; Yuli Rahmawati; Vina Iasha (Jurnal Basicedu, 2022)
This article has aimed to investigate the scientific literacy achievement of fourth-grade elementary school students. The research used a qualitative method with data collection techniques in interviews and open questions. This study involved a fourth-grade teacher and fourth-graduate students. Based on the existing theoretical framework, an assessment tool was developed, which measurement's ability to: a) recognize scientific concepts (nominal literacy);  b) define some key concepts (functional literacy);  c) use their understanding of scientific concepts to explain phenomena (conceptual literacy);  and d) use their knowledge Science to read a short article (multidimensional literacy). The study results found that the nominal literacy assessment showed the students' knowledge of Science was still limited. Functional literacy assessment can be seen students' interest in Science which is still minimal. Conceptual literacy assessment results in students' understanding of everyday scientific phenomena are still lacking, with multidimensional literacy can be assessed students' understanding of paragraph reading is still limited.